Marketing 1 - Blythe Jim; Coxhead Helene; Lashwood Martin; Partridge Lesley (Ft Knowledge, 2000)
What is Marketing, The Macro-Environment, The Task Environment, Marketing Strategy Within Corporate Strategy, Organisation of Marketing Activities, Further Reading and References.
What is Marketing, The Macro-Environment, The Task Environment, Marketing Strategy Within Corporate Strategy, Organisation of Marketing Activities, Further Reading and References.